Kinetics of Mixed Amino Acid and Ionic Liquid on CO2 Hydrate Formation - Bavoh, C.B. (Institute of Physics Publishing, 2019)
The formation of gas hydrate in oil and gas and carbon dioxide sequestration processing pipelines is unwanted and must be prevented for easy and safety processes. However, conventional kinetic hydrate inhibitors are less effective and thus, new inhibitors are required to effectively manage hydrate formation in the industry. Recently, ionic liquids and amino acids have been introduced as potential kinetic gas hydrate inhibitors (KHIs). But the quest for highly effective amino acids and ionic liquids hydrate inhibitors is still on going with no desired inhibition impact reported so far. Hence, a blend of these two classes of novel kinetic hydrate inhibitor may possibly perform better. Herein, the combined kinetic gas hydrate inhibition effect of some best performed amino acid (glycine) and ionic liquid (1-Ethyl-3-methy-limidazolium chloride) is reported on CO2 hydrate formation. The study was conducted in a sapphire hydrate cell using the constant cooling isochoric mode at 50/50 wt. concentration of glycine and 1-Ethyl-3-methy-limidazolium chloride at a total concentration of 1 wt.. All experiments were performed at 3.5 MPa and 274.15 K. The results showed that, all studied systems (pure glycine and 1-Ethyl-3-methy-limidazolium chloride and their mixture) inhibited CO2 hydrate formation by increasing its induction time and reducing the total moles of CO2 converted into hydrate. The inhibition impact of glycine was less than 1-Ethyl-3-methy-limidazolium chloride, but surprisingly their combined effect was less than 1-Ethyl-3-methy-limidazolium chloride but higher than glycine base on induction time and CO2 uptake evaluation. Â© Published under licence by IOP Publishing Ltd.